NURSES’ KNOWLEDGE OF GLASGOW COMA SCALE IN NEUROLOGICAL ASSESSMENT OF PATIENTS IN A TERTIARY CARE HOSPITAL - RAHMAT, M; RASHEED, M; BATOOL, S; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Neurological evaluation is a critical component of patient care, especially in tertiary care facilities where complex cases are often managed. The Glasgow Coma Scale (GCS) is a widely used tool for assessing the level of consciousness, particularly in patients with brain injuries, providing a standardized approach to evaluating neurological status. Objectives: This study aimed to evaluate nurses' knowledge of the GCS in neurological assessments of patients and to explore the relationship between nurses' knowledge of the GCS and demographic characteristics in a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted at Services Hospital Lahore. A sample of 80 nurses was selected through a convenience sampling method. Data were collected using structured questionnaires, and the analysis was performed using SPSS version 25, employing frequencies, percentages, and Chi-Square tests to examine associations. Results: Among the 80 nurses, the majority were female (75%) with an age distribution predominantly between 36-40 years (37%). Most nurses had 1-2 years of experience (37%) and held a General Nursing Diploma (37%). Knowledge levels varied, with 28% of nurses demonstrating poor knowledge, 46% having average knowledge, and 25% showing good knowledge of the GCS. Significant associations were found between knowledge levels and factors such as gender (p = 0.0001), qualification (p = 0.0000), experience (p = 0.0002), and department (p = 0.0001), while age showed no significant association (p = 0.423). Conclusion: The study revealed an average level of knowledge regarding the GCS among nurses, with significant associations between knowledge levels and demographic factors like gender, qualifications, experience, and department. These findings indicate the need for targeted educational interventions to improve nurses' understanding and application of the GCS, ultimately enhancing patient care in neurological settings.